Society and Law Enforcement Personnel in Trading Stolen Goods - Adiyatma, Septhian Eka; Purwoko, Naufal Giri; Pangestika, Finna Maessy; Kandiati, Dewi (Law Research Review Quarterly, 2020)
The existence of violating public order, as well as violation activities in accordance with article 480 of the Criminal Code are the characteristics of Kokrosono traders. The provisions of the article refer to criminal relief measures in terms of helping perpetrators of theft crimes obtain benefits from the results of their actions. The uniqueness of merchandise on Jalan Madukoro is that some traded goods are stolen goods. Capital of confidence in the thief makes the stock of stolen goods from the perpetrators of theft is always there. In this case, thieves and stolen merchants can automatically be subject to criminal penalties because there is an intentional element in them, different from the buyer who must be investigated first. This behavior can only be overcome with two channels, namely legal channels and non-legal channels. The legal route leads to regulations related to the detention activities in criminal law and to the extra-legal channels only as countermeasures before the event occurs. Significant differences regarding countermeasures between after and before are in their aftermath.